2021
DOI: 10.1002/aesr.202100016
|View full text |Cite
|
Sign up to set email alerts
|

B←N Coordination: From Chemistry to Organic Photovoltaic Materials

Abstract: Coordination between boron Lewis acid and nitrogen Lewis base (B←N) is a classically chemical issue that has been known for several decades. Recently, this B←N chemistry developed into a new stage toward electronic materials, e.g., adjusting optoelectronic properties of N‐based conjugated molecules via adding B Lewis acids, synthesizing B←N‐bridged conjugated units, and further constructing B←N‐embedded organic photovoltaic (OPV) materials. Herein, these progresses are systematically summarized starting from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 225 publications
(270 reference statements)
0
12
0
Order By: Relevance
“…[5,6] Having available one electron less for bonding interactions, boron compounds frequently feature low-lying lowest unoccupied molecular orbitals and small band gaps, characteristics that are beneficial for creating conjugated π-systems that find applications in bio-imaging, organic photovoltaics, field-effect transistors, and light-emitting diodes. [7][8][9][10][11] Moreover, the Lewis acidic character of tricoordinate boron allows for reversible binding of neutral and anionic substrates, which has drawn significant attention for organocatalysis, chemical sensing applications, and the development of stimuli-responsive smart materials. [12][13][14][15][16][17][18][19][20] While the molecular properties of boron species are advantageous in and of themselves, molecular aggregation and self-assembly into higher order structures frequently offer access to unique characteristics and novel functions.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Having available one electron less for bonding interactions, boron compounds frequently feature low-lying lowest unoccupied molecular orbitals and small band gaps, characteristics that are beneficial for creating conjugated π-systems that find applications in bio-imaging, organic photovoltaics, field-effect transistors, and light-emitting diodes. [7][8][9][10][11] Moreover, the Lewis acidic character of tricoordinate boron allows for reversible binding of neutral and anionic substrates, which has drawn significant attention for organocatalysis, chemical sensing applications, and the development of stimuli-responsive smart materials. [12][13][14][15][16][17][18][19][20] While the molecular properties of boron species are advantageous in and of themselves, molecular aggregation and self-assembly into higher order structures frequently offer access to unique characteristics and novel functions.…”
Section: Introductionmentioning
confidence: 99%
“…Organoboron chemistry provides new tools to design π-conjugated molecules and polymers. Jäkle’s, Chujo’s, Pammer’s, Huang’s groups, and our group have made great progress on organoboron A-type building blocks for conjugated polymers. The resulting polymers have been successfully used in OLEDs, OFETs, and OSCs. , Herein, we report a new A-type building block for conjugated polymers, namely, N–B←N bridged bithiophene (BNTzT). Its chemical structure is shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Organoboranes and organoboronic esters are versatile Lewis acids that readily coordinate to nitrogen-containing Lewis bases, which can be used to prepare inclusion complexes. The generally good stability at ambient conditions (air/water) and interesting physical and chemical properties has stimulated intense activity in the investigation of molecular boron←nitrogen (B←N) compounds. The strong covalent character, directionality, and reversible nature of the B←N bond make this interaction suitable also for diverse applications in supramolecular chemistry, particularly the self-assembly of finite and infinite aggregates. A series of recent investigations have shown that crystalline B ← N assemblies formed from triorganoboranes or organoboronic esters and pyridyl-donor ligands are suitable for selective molecular recognition of aromatics, the separation of petrochemicals, , the removal of harmful polycyclic aromatic hydrocarbons (PAHs), as well as the generation of luminescent , and semiconductor materials . Moreover, in the presence of alkenyl groups, [2+2] photocycloaddition reactions can be achieved, giving cyclobutanes in stereochemically pure form. , The common feature in these applications is the presence of cavities or channels in the crystalline solid matrix formed by the B←N assemblies…”
Section: Introductionmentioning
confidence: 99%